2018
DOI: 10.1161/strokeaha.117.019307
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance Clinical Triage for Acute Stroke Treatment

Abstract: The 3-step ACT-FAST algorithm shows higher specificity and reliability than existing scales for clinical LVO recognition, despite requiring just 2 examination steps. The inclusion of an eligibility step allowed recognition of endovascular-eligible patients with high accuracy. Using a sequential algorithmic approach eliminates scoring confusion and reduces assessment time. Future studies will test whether field application of ACT-FAST by paramedics to bypass suspected patients with LVO directly to endovascular-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 23 publications
0
29
1
13
Order By: Relevance
“…Comparing the FAST's validity features with previous study findings, Zhao et al (15) found that the sensitivity, specificity, and PPV of EMS personnel were 85.7%, 93.5%, and 80%, respectively, using FAST for the diagnosis of acute stroke in the pre-hospital emergency. Therefore, their study found more sensitivity and specificity than our study (15). In the study by Caceres et al (16), patients diagnosed with stroke by EMDs were transferred to the hospital significantly sooner than those not diagnosed with stroke by EMDs.…”
Section: Discussioncontrasting
confidence: 54%
“…Comparing the FAST's validity features with previous study findings, Zhao et al (15) found that the sensitivity, specificity, and PPV of EMS personnel were 85.7%, 93.5%, and 80%, respectively, using FAST for the diagnosis of acute stroke in the pre-hospital emergency. Therefore, their study found more sensitivity and specificity than our study (15). In the study by Caceres et al (16), patients diagnosed with stroke by EMDs were transferred to the hospital significantly sooner than those not diagnosed with stroke by EMDs.…”
Section: Discussioncontrasting
confidence: 54%
“…A very recent study by Zhao et al . in stroke[15] that describes a new algorithm called ACT-FAST which uses a three-step evaluation criteria that includes: (1) arm drift within 10 s, (2) language difficulty if left arm is affected or neglect if right arm is affected, and (3) stroke mimic screen. They found that they had an overall accuracy of 81.7%, the sensitivity of 85.7%, and specificity of 93.5% in identifying LVOs, which is higher than all other existing scoring models.…”
Section: Resultsmentioning
confidence: 99%
“…Using very conservative estimate of 10% eligible patients, the “mothership” hospital would face a deluge of patients to process to treat in order to perform ECR on 434 patients at MMC or 543 patients at RMH. A variety of tools are now available to screen patients for LVO (30, 31). However, a formal prospective field testing of these tools and the impact on hospital case load has not yet been evaluated.…”
Section: Discussionmentioning
confidence: 99%